Lasers for resurfacing - Rungsima Wanitphakdeedecha (2018)
© 2011 Springer-Verlag London Limited. Many signs of cutaneous photodamage are amenable to treatment with a variety of ablative and non-ablative lasers, light sources, and fractional photothermolysis. Ablative laser skin resurfacing offers the most substantial clinical improvement, but is associated with several weeks of postoperative recovery.